Modeling sporadic Alzheimer’s disease in mice by combining Apolipoprotein E4 risk gene with environmental risk factors - Ganesan, Kiruthika; Rentsch, Peggy; Langdon, Alexander; Milham, Luke T.; Vissel, Bryce (Frontiers in Aging Neuroscience, 2024)
Developing effective treatment for Alzheimer's disease (AD) remains a challenge. This can be partially attributed to the fact that the mouse models used in preclinical research largely replicate familial form of AD, while majority of human cases are sporadic; both forms differ widely in the onset and origin of pathology, therefore requiring specific/targeted treatments. In this study, we aimed to model sporadic AD in mice by combining two of the many risk factors that are strongly implicated in AD: ApoE4, a major genetic risk factor, together with an inflammatory stimuli. Accordingly, we subjected ApoE4 knock in (KI) mice, expressing humanized ApoE4, to low doses of Lipopolysaccharide (LPS) injections (i.p, weekly, for four months). We assessed these animals for behavioral impairments at 6 months of age using Open Field, Y-maze and Barnes Maze Test. LPS induced hypoactivity was observed in the Open Field and Y-maze test, whereas spatial learning and memory was intact. We then quantified differences in dendritic spine density, which is a strong correlate of AD. ApoE4KI mice showed a significant reduction in the number of spines after treatment with LPS, whereas there were no obvious differences in the total number of microglia and astrocytes. To conclude, in the current study the APoEe4 risk gene increases the vulnerability of hippocampal neurons to inflammation induced spine loss, laying a foundation for an early sporadic AD mouse model.